Modulation of the p38 MAPK Pathway by Anisomycin Promotes Ferroptosis of Hepatocellular Carcinoma through Phosphorylation of H3S10. (24th November 2022) - Chen, Wei; Yang, Wenjing; Zhang, Chunyan; Liu, Te; Zhu, Jie; Wang, Hao; Li, Tong; Jin, Anli; Ding, Lin; Xian, Jingrong; Tian, Tongtong; Pan, Baishen; et al.
Abstract : Hepatocellular carcinoma (HCC) is a prevalent malignant tumor worldwide. Ferroptosis is emerging as an effective target for tumor treatment as it has been shown to potentiate cell death in some malignancies. However, it remains unclear whether histone phosphorylation events, an epigenetic mechanism that regulates transcriptional expression, are involved in ferroptosis. Our study found that supplementation with anisomycin, an agonist of p38 mitogen-activated protein kinase (MAPK), induced ferroptosis in HCC cells, and the phosphorylation of histone H3 on serine 10 (p-H3S10) was participated in anisomycin-induced ferroptosis. To investigate the anticancer effects of anisomycin-activated p38 MAPK in HCC, we analyzed cell viability, colony formation, cell death, and cell migration in Hep3B and HCCLM3 cells. The results showed that anisomycin could significantly suppress HCC cell colony formation and migration and induce HCC cell death. The hallmarks of ferroptosis, such as abnormal accumulation of iron and elevated levels of lipid peroxidation and malondialdehyde, were detected to confirm the ability of anisomycin to promote ferroptosis. Furthermore, coincubation with SB203580, an inhibitor of activated p38 MAPK, partially rescued anisomycin-induced ferroptosis. And the levels of p-p38 MAPK and p-H3S10 were successively increased by anisomycin treatment. The relationship between p-H3S10 and ferroptosis was revealed by ChIP sequencing. The reverse transcription PCR and immunofluorescence results showed that NCOA4 was upregulated both in mRNA and protein levels after anisomycin treatment. And by C11-BODIPY staining, we found that anisomycin-induced lipid reactive oxygen species was reduced after NCOA4 knockdown. In conclusion, the anisomycin-activated p38 MAPK promoted ferroptosis of HCC cells through H3S10 phosphorylation.